Decapod crustaceans and fishes associating with echinoids at Los Cabos, Baja California Sur, Mexico - Hayes, Floyd (2022)
Introduction: The pointed spines of echinoids (sea urchins) provide shelter for a variety of facultative or obligatory ectosymbionts. Objective: To evaluate the hypothesis that decapods and fishes seek shelter among echinoids to reduce the risk of predation. Methods: We studied the frequency of decapod crustaceans and fishes associating with echinoids in shallow water (< 4 m) and deeper water (5-20 m) at Los Cabos, Baja California Sur, Mexico, during 1-6 January 2019. Results: Five species of decapods associated with three species of echinoids. Decapods in shallow water associated with the longest-spined species of echinoid, Diadema mexicanum, at a frequency 5.1 times higher than that of any other echinoid species, and with an average of 7.0 times more decapods per D. mexicanum than for any other echinoid species. Decapods in deeper water did not associate more frequently with D. mexicanum than with other echinoid species. The number of decapods per D. mexicanum was positively correlated with spine length of D. mexicanum. Fourteen species of fishes associated with four species of echinoids. Fishes in shallow water associated with D. mexicanum at a frequency 2.6 times higher than that of any other echinoid species, and with an average of 4.5 times more fishes per D. mexicanum than for any other echinoid species. Fishes in deeper water did not associate more frequently with D. mexicanum than with other echinoid species. The number of fishes per D. mexicanum was correlated with spine length of D. mexicanum. Decapods and fishes associated more frequently with echinoids in shallow water than in deeper water. Multiple individuals and species of decapods and fishes often associated together with a single D. mexicanum. One decapod species was an obligate associate of echinoids; the other decapod species and all fish species were facultative associates of decapods. Conclusion: Our results support the hypothesis that decapods and fishes seek shelter among the spines of echinoids to reduce the risk of predation by associating most frequently with the longest-spined species of echinoids and with the longest-spined individuals of the longest-spined species.